Vaccine repurposing approach for preventing COVID 19: can MMR vaccines reduce morbidity and mortality? - Anand Anbarasu; Sudha Ramaiah; Paul Livingstone (Taylor & Francis Group, 2020)
The coronavirus disease (COVID-19) is resulting in millions of infected individuals with several hundred thousands dead throughout the world. Amidst all the havoc, one interesting observation in the present COVID-19 pandemic is the negligible symptoms in the young; particularly children below 10 years of age. We assume the extensive pediatric vaccination with MMR vaccines followed globally could have resulted in innate immune responses, e.g., induction of interferons (IFNs) and activated natural killer (NK) cells, thereby offering natural immunity against SARS-CoV-2 in the young population. Possible cross-protective innate immunity offered by MMR vaccination prompted us to suggest repurposing MMR vaccination for immuno-prophylaxis against COVID-19.